Tourists’ Preferences for Sustainable Tourism: The Case of Pok Tunggal Beach, Yogyakarta Indonesia - Saptutyningsih, Endah; Duanta, Aprio (Jurnal Ekonomi & Studi Pembangunan, 2021)
Tourists as the main actor in tourism industry play an essential role in achieving sustainable tourism. Tourist preference for physical environment and infrastructure development in the tourism destination can affect the achievement of sustainable tourism. This study aims at measuring tourist preference for sustainable tourism management and calculating the economic value of the tourism destination. For this purpose, the Pok Tunggal Beach tourist area in Yogyakarta Indonesia was considered as a case study site. A survey with 200 local tourists was conducted using the Choice Modeling (CM) technique to measure their preferences related to the development on the beach. This study found that tourists prefer to pay more fees to get better and more sustainable facilities. The economic value of the Pok Tunggal Beach is the amount of IDR 1,038,600 (USD 73.66). The main attributes in the destination, tourist's education, environmental awareness, and recreation costs are statistically significant in determining tourists' preferences. This study recommends Pok Tunggal beach quality improvement by considering the tourist preferences. This study also suggests a price for the entrance fees, not only to increase revenue but also to monitor and control the number of tourists who visit the beach.